2019
DOI: 10.1093/ptj/pzz051
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Spinal Cord Stimulation and Top-Down Nociceptive Inhibition in People With Failed Back Surgery Syndrome: A Cohort Study

Abstract: BackgroundDescending nociceptive inhibitory pathways often malfunction in people with chronic pain. Conditioned pain modulation (CPM) is an experimental evaluation tool for assessing the functioning of these pathways. Spinal cord stimulation (SCS), a well-known treatment option for people with failed back surgery syndrome (FBSS), probably exerts its pain-relieving effect through a complex interplay of segmental and higher-order structures.ObjectiveTo the best of our knowledge, no clinical studies have thorough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Two articles used an indirect evaluation through experimental pain measurements with Conditioned Pain Modulation (CPM). CPM is an indirect psychophysical measure to assess the functioning of the endogenous descending nociceptive inhibitory system, whereby SCS seemed to activate this descending system [50,66]. Additionally, sensory assessments with mechanical and thermal hypersensitivity indicated that SCS reduced hypersensitivity [5,23,29], indicative for the activation of brainstem structures in the descending inhibition.…”
Section: Scientific Support For This Hypothesismentioning
confidence: 99%
“…Two articles used an indirect evaluation through experimental pain measurements with Conditioned Pain Modulation (CPM). CPM is an indirect psychophysical measure to assess the functioning of the endogenous descending nociceptive inhibitory system, whereby SCS seemed to activate this descending system [50,66]. Additionally, sensory assessments with mechanical and thermal hypersensitivity indicated that SCS reduced hypersensitivity [5,23,29], indicative for the activation of brainstem structures in the descending inhibition.…”
Section: Scientific Support For This Hypothesismentioning
confidence: 99%
“…10 Interactions are established by (1) baroreflex activity with an inverse relationship between resting blood pressure levels and acute pain sensitivity, 11 (2) the vagal-nociceptive interactions where sympathetic and parasympathetic preganglionic nuclei receive input from the descending nociceptive inhibitory pathways to exert an influence on pain thresholds and modifying autonomic outflow, 50,58 and (3) projections from the periaqueductal grey neurons to autonomic centers in the medulla, involved in cardiovascular changes during endogenous analgesia. 6,34 Because structural and functional brain alterations are reported in chronic pain patients, 42 as well as a dysregulation of the balance between the sympathetic and parasympathetic system, 17,20 decreased baroreflex sensitivity, 19 and diminished functioning of the descending nociceptive inhibitory pathways, 31,45 both systems demonstrated altered output mechanisms, which points towards a relation between pain intensity and HRV in chronic pain. Nevertheless, despite these anatomical and functional connections, no information is available yet concerning the association between the amount of pain intensity and HRV parameters in patients with chronic pain.…”
Section: Introductionmentioning
confidence: 99%
“…Because structural and functional brain alterations are reported in chronic pain patients, 42 as well as a dysregulation of the balance between the sympathetic and parasympathetic system, 17,20 decreased baroreflex sensitivity, 19 and diminished functioning of the descending nociceptive inhibitory pathways, 31,45 both systems demonstrated altered output mechanisms, which points towards a relation between pain intensity and HRV in chronic pain. Nevertheless, despite these anatomical and functional connections, no information is available yet concerning the association between the amount of pain intensity and HRV parameters in patients with chronic pain.…”
Section: Introductionmentioning
confidence: 99%